2022
DOI: 10.1177/15248380221129589
|View full text |Cite
|
Sign up to set email alerts
|

Risk Markers for Victimization and Perpetration of Male-to-Female Physical Intimate Partner Violence in Sub-Saharan Africa: A Meta-Analysis

Abstract: Exposure to intimate partner violence (IPV) incurs significant public health consequences. Understanding risk markers can accelerate prevention and response efforts, important in settings like Sub-Saharan Africa (SSA) where resources are scarce. In this study, four databases were searched to identify studies that examined risk markers for male-to-female physical IPV. With application of the socioecological model, we analyzed 11 risk markers for male physical IPV perpetration (with 71 effect sizes) and 16 risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…Further, those who witnessed IPV were more likely to report the combination of IPV victimization and perpetration than to report either victimization or perpetration alone. These findings align with prior research documenting witnessing IPV in parental relationships as a key risk factor for women's victimization from IPV in adulthood, in sub-Saharan Africa, East Asia and the Pacific, and South Asia ( Ackerson & Subramanian, 2009 ; Fry et al, 2012 ; Mootz et al, 2022 ; Stake et al, 2020 ). It also extends prior research that demonstrates an association between witnessing parental IPV as a girl and using IPV (i.e., perpetration) as an adult woman, an area of inquiry that has largely been limited to studies from high income countries (HICs) or on male perpetration alone in low and middle income country (LMIC) contexts ( Fonseka et al, 2015 ; Islam et al, 2017 ; Kimber et al, 2018 ).…”
supporting
confidence: 88%
“…Further, those who witnessed IPV were more likely to report the combination of IPV victimization and perpetration than to report either victimization or perpetration alone. These findings align with prior research documenting witnessing IPV in parental relationships as a key risk factor for women's victimization from IPV in adulthood, in sub-Saharan Africa, East Asia and the Pacific, and South Asia ( Ackerson & Subramanian, 2009 ; Fry et al, 2012 ; Mootz et al, 2022 ; Stake et al, 2020 ). It also extends prior research that demonstrates an association between witnessing parental IPV as a girl and using IPV (i.e., perpetration) as an adult woman, an area of inquiry that has largely been limited to studies from high income countries (HICs) or on male perpetration alone in low and middle income country (LMIC) contexts ( Fonseka et al, 2015 ; Islam et al, 2017 ; Kimber et al, 2018 ).…”
supporting
confidence: 88%
“…Combined, these findings align with calls to clarify the link between mental health and IPV outcomes (Stark et al, 2023) and support is growing. In the aforementioned meta-analysis, PTSD and depression were among the strongest risk markers for IPV victimization (Mootz et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Even so, the actual strength of SES factors is not clear. A meta-analysis of risk markers of physical IPV victimization and perpetration among adults in SSA found demographic factors were not significantly associated with either outcome (Mootz et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of 207 studies examined mental health indicators of IPV and found that common mental disorders and antisocial and borderline personality disorder were associated with both perpetration and victimization ( Spencer et al, 2019 ). Our team conducted a meta-analysis of 51 studies from sub-Saharan Africa to identify risk markers for IPV ( Mootz et al, 2022 ). For men, there were small effect sizes for IPV perpetration and substance use and medium to large effect sizes for witnessing parental IPV and being abused as a child, potential indicators of other mental health struggles ( Wathen and MacMillan, 2013 ).…”
Section: Introductionmentioning
confidence: 99%